PUSAT KREATIF DAN PENGOLAHAN FESYEN DAN MISELIUM BANDUNG - Fransisca Meilanny; Timmy Setiawan (Jurusan Arsitektur dan Perencanaan, 2021)
Fast fashion is a phenomenon, where the latest trends and high levels of consumer demand affect the amount of fashion production. This affects the production chain system and the lifestyle of modern society, especially the gen z and gen y (millennials). The mass production that occurs causes the need for many resources and the use of low-quality (non-durable) materials to pursue trends and affordable prices. Plus the lifestyle of modern society which tends to follow trends has led to a linear concept in fashion, namely take-wear-throw. This system certainly has an impact on environmental damage, especially on materials that are difficult to decompose. This phenomenon has led to community innovations related to mushroom technology that produces mycelium as an environmentally friendly material as well as efforts made by a creative community in fashion management. Thus, it is hoped that the architecture can act as a container that supports activities by applying the cradle-to-cradle (upcycling) concept. This concept invites the public, especially modern society, to be more aware of the management and use of fashion which is supported by a metaphorical method approach of combining mushroom and fashion characters with the use of alternative materials such as mycelium which is the root of mushrooms which is an environmentally friendly material, as well as programs from processing mushrooms and fashion to create an activity center that has a positive impact on the environment and society by promoting ecological balance. Keywords: Architecture; Creative; Environmental Damage; Fast fashion; Mycelium AbstrakFesyen cepat merupakan sebuah fenomena, dimana tren terbaru dan tingkat permintaan tinggi konsumen yang berpengaruh terhadap jumlah produksi fesyen. Hal ini mempengaruhi sistem rantai produksi dan gaya hidup masyarakat modern, terutama kaum gen z dan gen y (milenial). Produksi massal yang terjadi menyebabkan banyaknya sumber daya yang dibutuhkan dan penggunaan material yang berkualitas rendah (tidak tahan lama) untuk mengejar tren dan harga terjangkau. Ditambah gaya hidup masyarakat modern yang cenderung mengikuti tren menyebabkan konsep linear dalam fesyen, yaitu ambil-pakai-buangj. Sistem ini tentunya berdampak pada kerusakan lingkungan, khususnya pada material yang sulit terurai. Fenomena ini memunculkan inovasi masyarakat terkait dengan teknologi jamur yang menghasilkan miselium sebagai material ramah lingkungan serta upaya yang dilakukan oleh suatu komunitas kreatif dalam pengelolaan fesyen. Dengan demikian, diharapkan arsitektur dapat berperan sebagai wadah yang menunjang aktivitas dengan penerapan konsep cradle-to-cradle (upcycling). Konsep ini mengajak masyarakat, khususnya masyarakat modern untuk lebih sadar akan pengelolaan dan pemanfaatan fesyen yang di dukung dengan pendekatan metode metafora penggabungan karakter jamur dan fesyen dengan penggunaan material alternatif seperti miselium yang merupakan akar dari jamur yang merupakan material yang ramah lingkungan, serta program dari pengolahan jamur dan fesyen untuk mewujudkan pusat aktivitas yang berdampak pada lingkungan dan masyarakat secara positif dengan mengusung keseimbangan ekologi.